The fatigue behaviour of the breathing webs of steel bridge girders - Škaloud, Miroslav; Zörnerová, Marie (Journal of Civil Engineering and Management, 2005)
The limit state of thin‐walled steel girders subjected to many times repeated loading is to a great extent affected by the cumulative damage process occurring in the girder webs “breathing” under the repeated loads. Based on experimental results obtained by the authors at the Institute of Theoretical and Applied Mechanics in Prague, (i) various approaches to the definition of the fatigue limit state of the above girders are discussed, (ii) a number of potential design procedures suggested by other researchers validated and (iii) a set of S‐N curves, established by the writers so as to serve as a reliable tool for the fatigue analysis of thin‐walled girders with “breathing” webs, presented. Plieninių tilto sijų „alsuojančių“ sienelių nuovargio būsena Santrauka. Plonasienių plieninių sijų, apkrautų kartotinėmis apkrovomis, ribinis būvis iš dalies yra veikiamas didėjančio sijos sienelės, “alsuojančios” nuo kartotinų apkrovų, irimo. Remdamiesi Prahos teorinės ir taikomosios mechanikos institute savo atliktais bandymų rezultatais autoriai: 1) aptaria įvairius požiūrius į minėtų sijų nuovargio ribinių būvių nustatymą; 2) pagrindžia kitų tyrinėtojų pasiūlytus projektavimo metodus; 3) pateikia savo sudarytų S‐N kreivių rinkinį, kuris būtų patikima priemonė analizuoti plonasienių sijų su “alsuojančiomis” sienelėmis nuovargiui. Reikšminiai žodžiai: kartotinės apkrovos, sienelių “alsavimas”, nuovargio plyšiai, irimo mechanizmas, nuovargio ribinis būvis, S-N kreivės. First Published Online: 14 Oct 2010